Разрешение ряда случаев сомнительной видовой самостоятельности среди циклопообразных (Crustacea, Cyclopoida) - Монченко, В.И. (Вестник зоологии, 1988)
Eight pairs of species group taxa, previously considered by different authors as species. subspecies or intrasubspeci fie forms, are established to be bona species due to discovered sympatry of each pair within the same waterbody (wells, springs etc.). Both fresh-water Diacyclops clandestinus Kieffer and brackish-water D. cf. clandestinus from Caucasus river Black Sea estuaries (Monchenko, 1982) do not bear exopod seta on antenna II (that Petkovsky, 1984. erroneously ascribed to the latter).